UPAYA SEKOLAH DASAR ISLAM TERPADU (SDIT) TAWAKKAL DALAM MENUMBUHKAN RASA PERCAYA DIRI SISWA - Milla Fizcha Aulia; Mega Isvandiana Purnamasari; Afid Burhanuddin (Scholarly Journal of Elementary School, 2026)
This study aims to: (1) Describe the efforts made by SDIT Tawakkal in fostering students' self-confidence; and (2) Analyze the impact of efforts to foster self-confidence on student development at SDIT Tawakkal. Self-confidence is an important aspect in children's development that influences their courage to speak, take the initiative, and actively participate in academic and non-academic activities. Therefore, understanding the school's strategy in building students' self-confidence is the main focus of this study. This study uses a qualitative approach with a descriptive method. The subjects of the study included the principal, teachers and students at SDIT Tawakkal. Data collection techniques were carried out through observation, interviews, and documentation. The results of the study showed that SDIT Tawakkal implemented various strategies in fostering students' self-confidence, such as through religious programs, experience-based learning, and various extracurricular activities, market days, cooking classes, academic and non-academic activities. These efforts have a positive impact on increasing students' courage to speak, take the initiative, and actively participate in academic and non-academic activities. In addition, support from teachers and the school plays a very important role in strengthening students' self-confidence.